(untitled) (Journal of actual problems of jurisprudence, 2018)
Insurance as system of protection of property interests of citizens, the organizations and the state is a necessary element of modern society. It provides guarantees of restoration of the broken property interests in case of natural and technogenic catastrophes, other unforeseen phenomena. Insurance allows not only to pay the suffered losses, but also is one of the stablest sources of financial resources for investments. All this defines a strategic position of insurance in the countries with the developed market economy. In modern Kazakhstan an important task is formation of the civilized insurance market. Key words: insurance, insurance market, insurance activity, insurance legislations.